Necesidad de insertar el principio de proporcionalidad y la no aplicación de trascendencia penal por cuanto la pena no puede trascender de la persona del delincuente en relación a la prescripción de las penas restrictivas y no privativas de libertad señalada en el art. 75 numeral 1 y 2 del código orgánico integral penal - Gómez Granda, José Patricio (2016)
Article 75 of the Comprehensive Criminal Code provides that the sentence prescribed, in accordance with paragraph 1, as to the restrictive sentences of freedom prescribed in the time of the maximum penalty of deprivation of liberty provided for in the criminal type, more Fifty percent, this is for the time of the maximum of the criminal type plus fifty percent, it being understood that this number of years for the criminal type runs the prescription for fugitives or those who have broken the sentence, since Art 74 clause 1 of the Comprehensive Penal Code, states that the limitation period is extinguished when the sentence has been fully complied with in any of its forms. The legal institution of prescription, is a means used by people, to evade justice and criminal action, who in committing a crime flee and hide so as not to be tried and sentenced for the conduct of unlawful conduct, which action Yes, it is a situation that brings legal and personal consequences, because the prescription for the lapse of the sentence of the criminal type is too long, and worse still taken into account plus fifty percent, which means an accumulation of penalties For the prescription, that therefore is contrary to the rights and dignity of the people. 5The prescription of the penalty for the time of the criminal type, is very widespread therefore violent human rights of personal dignity, because that like all have a family that will suffer from being fleeing from the same justification for the time Criminal offense